1991
DOI: 10.1002/zaac.19915940111
|View full text |Cite
|
Sign up to set email alerts
|

Bis(perfluor‐n‐hexyl)‐ und Bis(perfluor‐n‐octyl)cadmium: Darstellung, Eigenschaften, NMR‐spektroskopische und massenspektrometrische Untersuchungen

Abstract: Die Perfluoralkylcadmium‐Verbindungen Cd(C6F13)2 und Cd(C8F17)2 werden sowohl unkomplexiert als auch als Komplexe mit DMF, CH3CN, Glyme und Diglyme dargestellt. Die Reaktionsgeschwindigkeit der Cd(Rf)2‐Verbindungen mit PhHgCl nimmt mit der durch Leitfähigkeitsmessungen in verschiedenen Lösungsmitteln bestimmten Dissoziation zu. Die NMR‐sowie die Massenspektren werden diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

1995
1995
2001
2001

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…However, it must be suggested that In(C 2 H 5 ) 2 R f derivatives and In(C 2 H 5 ) 3 are strong Lewis-acids that completely bond the stoichiometric amounts of N(C 2 H 5 ) 3 . It remains unintelligible that even in the presence of a twofold or threefold excess of N(C 2 H 5 ) 3 no spectroscopic evidence for the quarternary ammonium salt was found.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, it must be suggested that In(C 2 H 5 ) 2 R f derivatives and In(C 2 H 5 ) 3 are strong Lewis-acids that completely bond the stoichiometric amounts of N(C 2 H 5 ) 3 . It remains unintelligible that even in the presence of a twofold or threefold excess of N(C 2 H 5 ) 3 no spectroscopic evidence for the quarternary ammonium salt was found.…”
Section: Resultsmentioning
confidence: 98%
“…The reactions of R f I with In(C 2 H 5 ) 3 with the exception of those of C 2 F 5 I had in common, that one ethyl group was exchanged for one perfluoroorgano group, even if a large excess of the perfluoroiodoalkane was used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations